Uma análise de sentido do poema Lamento Oculto de um Surdo, de Shirley Vilhalva - Melo, Rafael Paulo de Ataíde Monteiro (2021)
In this dissertation, I develop a discourse analysis guided by the analysis categories of Bakhtin's Theory, in Shirley Vilhalva's poem Lamento Oculto de um Deaf, corroborating the Cultural, Historical, Political and Social growth of the Deaf Community. I present research contributions developed in the field of Literature, Deaf Literature, Deaf Culture, Visual Literature, such as: the contributions of Eagleton (2006), Wrigley (1996), Peixoto (2016), Nascimento (2006), Karnopp (1999), Skliar (1998) and others. From the analysis of the meaning of the poem, through bibliographic studies related to the Deaf Community and its Literature, I search in the categories of analysis provided by Bakhtin's Theory, the historical, cultural, social, political and ideological relationship of the Deaf Community towards the Community Listener. The motivations for this research are given by the need for this Deaf Community to wake up to poiesis (creation) of their own literary productions, looking at the "I" (deaf community) and to the "other" (hearing community), finding themselves in the other and in herself, in a dialogical relationship between “me and the other”. As a general objective, I intended to analyze the meanings present in the corpus, which directly influence the militancy of the Deaf Community. As specific objectives, broadly study Bakhtin's theory and its categories; describe the constructions of meaning in the written poem based on Bakhtinian categories and, finally, extract from the descriptions cultural, social, historical and political expressions present in the poem. The research has a Discourse Analysis approach, using the categories of Bakhtin's Theory: Authorship, Ideology, Style and Aesthetics, Polyphony and Chronotopy to extract and describe, within the universe of meaning, the power relationship between Deaf Communities and Listener. In the analysis results, I highlight the universe of meaning contained in the poem, evidencing the categories of Bakhtin's Theory in the corpus excerpts. Therefore, Deaf Literature is narrated as an area of knowledge in different spaces, both in formal and informal social environments, in signed or written text, paintings and poems, representing and recording a diverse audience in Culture, History, Social, Ideology and the Militance of a people that seeks to seal its voice as a Deaf Community. With this work it is expected to highlight the Deaf Literature and the experiences of the Deaf Community, thus contributing to the education of the deaf, with the academy and society.